2018
DOI: 10.1108/mabr-11-2017-0029
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing operational risks in container shipping systems by using cognitive assessment technique

Abstract: Purpose-This paper aims to propose a technique based on cognitive assessments to quantify identified operational risks from the perspective of container shipping or logistics system administrators. The results derived from the risk quantification could be used to prioritize risks as well as support the decision-making process in risk prevention and mitigation. Design/methodology/approach-This paper identified container shipping operational risks (CSORs) from a logistics perspective. A multivariate risk evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
(149 reference statements)
0
22
0
Order By: Relevance
“…Literature review has been used by scholars as a method for the identification of CSORs (Nguyen and Wang, 2018; Chang et al , 2015). This study looks into (1) The literature of blockchain technical research; (2) The reports from blockchain adopters, solution providers and specialized institutions; and (3) Observed incidents of blockchain applications and CSORs, to identify the potential HEs that may occur with blockchain integrated systems.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Literature review has been used by scholars as a method for the identification of CSORs (Nguyen and Wang, 2018; Chang et al , 2015). This study looks into (1) The literature of blockchain technical research; (2) The reports from blockchain adopters, solution providers and specialized institutions; and (3) Observed incidents of blockchain applications and CSORs, to identify the potential HEs that may occur with blockchain integrated systems.…”
Section: Methodsmentioning
confidence: 99%
“…sensors).Unexpected decrease in transport quantity – 3_QaDe : This CSOR was identified by Chang et al (2015) and can be triggered by the situation of information asymmetry as the competitors might have better information to make their decisions in freight offering.Detainments and other legal liabilities related to cargo content – 3_DmLi : Chang et al (2015) and many events, in reality, indicated that the content of cargo, when being hidden or misdeclared could cause ship detainments, delays of voyages, port skipping and other legal liabilities to ocean carriers or freight forwarders.Cargoes accidents – 3_CgAc : HEs related to cargoes inside containers are various. Apart from well-known accident types such as fires and explosions, other phenomena are also possible to happen, such as cargo liquefaction, leakage and corrosion (Tseng et al , 2013; Nguyen and Wang, 2018). …”
Section: Operational Risks Of Blockchain-enabled Systemsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they have not come to a common consensus on container operational risk dimensions [11]. The extant literature shows that the lack of management commitment of the shipping company to container handling is a typical dimension for container operational risk [15][16][17]. Drewry [18] indicated that the risk factors related to container logistics operations dimensions could be categorized into seven themes: booking and invoicing errors, documentation, errors in customs regulatory compliance and security compliance, theft Sustainability 2021, 13, 9248 2 of 21 and cargo loss or damage, strikes and transport congestions, piracy, and terrorist attack.…”
Section: Introductionmentioning
confidence: 99%